International capital flows and speculation - Rob Hayward; Andros Gregoriou (Journal of Risk and Financial Management, 2021)
In response to questions about the relative importance of different types of capital flow for international competitiveness, we develop a structural vector auto-regressive model of the real exchange rate and international capital flows. We reveal that innovations to speculative sentiment cause changes in competitiveness. We report that speculation replaces the effect of equity, bond and most of the interest rate effect. The results show that international speculative sentiment is an important contributor to exchange rate and that monetary and regulatory authorities should find ways of measuring and understanding banking and financial flows.
Keywords: C32; F31; F32; G15; 330; capital flow; currency crisis; exchange rates; VAR